Los contenidos televisivos de los canales locales y su incidencia en el fortalecimiento de las tradiciones montubias en el cantón Babahoyo, Provincia de Los Ríos - González Mora, Luis Eduardo (2019)
The study of the present research is based on improving the quality and increasing the frequency of local television content aimed at strengthening Montubian traditions in the Babahoyo canton, likewise, it is expected to generate a theoretical contribution that will serve to guide future research related to the subject and a practical contribution to help and guide those who administer the local channels and adequately strengthen Montubian traditions. Ecuadorian customs are based on their ethnic and regional diversity recognized by the National Assembly. His knowledge is diluted in these modern times, where technology advances and takes control of our lives, despite this dead letter and the different cultural and social activities where the different traditional forms of Montubia family coexistence are put into practice. Fluminense, its diffusion is null by the media, especially television. Ethnic content should be included and improved in local television media so that they do not limit Montubian traditions, but rather shape their cultural identity from the population of the Babahoyo canton, Los Ríos Province.